Commission of Inquiry collecting evidence of war crimes committed by all sides in Israel and Occupied Palestinian Territories - OHCHR (UN Independent International Commission of Inquiry on the Occupied Palestinian Territory, 2023)
There is already clear evidence that war crimes may have been committed in the latest explosion of violence in Israel and Gaza, and all those who have violated international law and  targeted civilians must be held accountable for their crimes.
Keywords: 2023-10 October